KAJIAN KEARIFAN LOKAL TRADISI MARSATTAN/MANGUPA (MEMINTA KESELAMATAN) PADA MASYARAKAT MANDAILING DESA GUNUNG MALINTANG KECAMATAN BARUMUN TENGAH KABUPATEN PADANG LAWAS - Nuriza Dora Ijtimaiyah Jurnal Ilmu Sosial dan Budaya) (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2020)
AbstractThis study aims to obtain data or information and analyze in regard to local wisdom in preserving Marsattan / Mangupa tradition in the Gunung Malintang village community in Barumun Subdistrict, Padang Lawas Regency. Research result shows: 1) Community knowledge about the need to implement the marsattan / mangupa tradition in a compilation community provoking women (haroan boru) and inviting new homes to ask for safety, sustenance and being kept away from distress assistance 2) Community understanding of local wisdom in the implementation of the marsattan / mangupa tradition much needed, because the marsattan tradition is one of the traditions that is still maintained and preserved by the community 3) the marsattan / mangupa tradition has become the custom of the people of the village of Gunung Malintang and is still quite good and still holds fast to this tradition as seen from the community's habit of always carrying this tradition a compilation of boys bringing brides to their homes, Opening a new home 4) Gunung Malintang village community believes the implementation of this tradition can be far away disastrously disastrously with advice given by relatives to the bride and groom of the new home